Fate of density waves in the presence of a higher-order van Hove singularity - Alkistis Zervou; Dmitry Efremov; Joseph Betouras (2023)
Topological transitions in electronic band structures, resulting in van Hove singularities in the density of states, can considerably affect various types of orderings in quantum materials. Regular topological transitions (of neck formation or collapse) lead to a logarithmic divergence of the electronic density of states (DOS) as a function of energy in two dimensions. In addition to the regular van Hove singularities, there are higher-order van Hove singularities (HOVHS) with a power-law divergence in DOS. By employing renormalization group techniques, we study the fate of a spin-density wave phase formed by nested parts of the Fermi surface, when a HOVHS appears in parallel. We find that the phase formation can be boosted by the presence of the singularity, with the critical temperature increasing by orders of magnitude, under certain conditions. We discuss possible applications of our findings to a range of quantum materials such as Sr3Ru2O7, Sr2RuO4, and transition metal dichalcogenides.